Bullous erythema multiforme post Corbevax anti-COVID-19 vaccine: case report. - Dave, M.; Mehta, H.; Nimbark, D. (European Journal of Pediatric Dermatology, 2022)
Vaccination against COVID-19 is key to reducing the impact of the disease. However, both COVID-19 and its vaccination can cause skin reactions. There are studies showing a link between erythema multiforme and COVID-19 infection; in some cases erythema multiforme can follow the anti-COVID-19 vaccination. The current report describes a case of bullous erythema multiforme that developed in a teenager after the Corbevax vaccine.